Analysis and Calculation of Power System for Medium Voltage AC Electric Propulsion Ship. (October 2020) - Wei, Jiang; Zhuo, Chen
Abstract: This paper introduces the advantages of integrated electric propulsion system in large and medium-sized ships. The short circuit current, grounding fault, harmonic and voltage drop in the design of medium voltage AC integrated power system are calculated and analyzed. Taking a real ship as an example, the power system design is completed.